2016
DOI: 10.1039/c6tb00612d
|View full text |Cite|
|
Sign up to set email alerts
|

Tunable self-assembly of Irinotecan-fatty acid prodrugs with increased cytotoxicity to cancer cells

Abstract: The development of a clinical chemotherapeutic is not an easy task. One challenge is how to deliver the agent to cancer cells. Nano-formulation of prodrugs, which combines the strengths of nanotechnology and prodrugs, possesses many advantages for chemotherapeutic drug delivery, including high drug loading efficiency, improved drug availability and enhanced accumulation in cancer cells. Here, we have constructed a small library of Irinotecan-derived prodrugs, in which the 20-hydroxyl group was derived with fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…High hydrophilic content always tends to afford filamentous structures, while lower hydrophilic content prefers rod-like or spherical structures. 45, 56, 57 As a result, uniform nanorods were obtained at higher HCPT to Ce6 ratios through the confinement of the core HPCT nanostructure with an energy minimization process. It has been reported that cylindrical nanostructures exhibit very good pharmacokinetics and efficiency in drug delivery even better than spherical ones because of their multiple endocytotic mechanisms, enhanced internalization rates and effective adhesion to cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High hydrophilic content always tends to afford filamentous structures, while lower hydrophilic content prefers rod-like or spherical structures. 45, 56, 57 As a result, uniform nanorods were obtained at higher HCPT to Ce6 ratios through the confinement of the core HPCT nanostructure with an energy minimization process. It has been reported that cylindrical nanostructures exhibit very good pharmacokinetics and efficiency in drug delivery even better than spherical ones because of their multiple endocytotic mechanisms, enhanced internalization rates and effective adhesion to cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…Take advantage of this emerging strategy, a few chemotherapeutic agents (e.g., paclitaxel, doxorubicin, SN38, curcumin) have reported to be formulated as PNDs for enhanced anticancer therapy. 4045 There is no doubt that the rationale of PNDs has shown great promise to be regarded as next generation of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic anticancer drug irinotecan (Ir) was esterified with fatty acid with different alkyl chain lengths yielding a small library of irinotecan‐fatty acid prodrugs (Ir‐5 C, Ir‐8 C and Ir‐12 C) and subsequent self‐assembly in aqueous environment resulted into nanoformulation of Ir‐fatty acid units (Figure ) and are hydrolyzed by carboxyesterases . Nanoformulation resulted in higher hydrophilicity, enhanced drug loading capacity and higher level accumulation in cancer cells.…”
Section: Biomolecular Nanodrug Formulationsmentioning
confidence: 95%
“…142 Similarly, a lipidated Irinotecan prodrug was developed by Liang and co-workers that demonstrated increased cytotoxicity in cancer cells. 143 A similar process was also used to develop cytarabine nanoparticles through the conjugation of hexanoic acid. This system exhibited an increased cellular uptake in comparison to the native drug, improving in vitro the cytotoxicity of the drug.…”
Section: Small Molecule Sapdsmentioning
confidence: 99%